2019
DOI: 10.1016/j.apsusc.2019.06.203
|View full text |Cite
|
Sign up to set email alerts
|

Identifying surface structural changes in a newly-developed Ga-based alloy with melting temperature below 10 °C

Abstract: Surface oxidation, as one of fundamental chemical reactions in metals, greatly affects their properties. Herein, we develop a new quaternary GaInSnZn liquid metal with the melting temperature of 9.7 C, which is the lowest among all reported Ga-based liquid metals. With high-resolution transmission electron microscopy, we directly observed the oxide layer formed on the surface of the liquid metal. The initially formed oxide layer is revealed to be amorphous and very sensitive to electron beam. Prolonged irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Among various candidate materials, Ga and Ga-based liquid metal (LM), as a new room-temperature liquid state, have received unique attention in recent years. The unique self-healing property of Ga-based LM can effectively prevent the structural collapse and particle pulverization during lithiation/delithiation processes and thus achieve a long cycle life . Unfortunately, the bulk Ga-based LM is difficult to directly apply on the current collector due to its high surface energy, , which also suffers from volume expansion and the long diffusion length of Li + during the lithiation process, leading to poor cycling and rate performance. Therefore, new strategies are urgently needed to solve these problems for bulk Ga-based LM.…”
Section: Introductionmentioning
confidence: 99%
“…Among various candidate materials, Ga and Ga-based liquid metal (LM), as a new room-temperature liquid state, have received unique attention in recent years. The unique self-healing property of Ga-based LM can effectively prevent the structural collapse and particle pulverization during lithiation/delithiation processes and thus achieve a long cycle life . Unfortunately, the bulk Ga-based LM is difficult to directly apply on the current collector due to its high surface energy, , which also suffers from volume expansion and the long diffusion length of Li + during the lithiation process, leading to poor cycling and rate performance. Therefore, new strategies are urgently needed to solve these problems for bulk Ga-based LM.…”
Section: Introductionmentioning
confidence: 99%
“…We detected metallic bonded Ga, In, and Sn, thus we infer that the oxide layer was less than 10 nm thick. The thickness and composition of the surface oxide of a similar newly developed Ga-In-Sn-Zn liquid alloy have been characterized by TEM and XPS [20]. There, the authors reported on the effect of electron beam exposition time on the growth of a ZnGa2O4 layer.…”
Section: Resultsmentioning
confidence: 99%
“…As a preliminary study of Field’s metal, a chemical characterization of the oxide surface of Field’s metal was carried out using X-ray Photoelectron Spectrometry (XPS), performed using a Thermo-Scientific “K-Alpha” equipment, and the obtained data were analysed with Avantage Data System software to determine the composition of the oxide layer. Differential Scanning Calorimetry (DSC) was used to obtain its thermal parameters [ 32 , 33 ] using a Wettler-Toledo DSC822e DSC at a heating and cooling rate of 10 K/min over a temperature range from 298 to 348 K.…”
Section: Methodsmentioning
confidence: 99%